Analisis Pengetahuan, Sikap Dan Motivasi Kepatuhan Dokter Spesialis Dengan Pengisian Rekam Medis Pasien di Instalasi Rawat Inap RS X Jakarta - Anita Sriwaty Pardede (Lembaga Pengembangan Kinerja Dosen, 2024)
Completeness in filling of medical record files by doctors will be able to facilitate other health workers in providing action or treatment to patients, and can be used as a source of data in the Medical Record section in data management and reports that will be used as useful information for hospital management in determining evaluation and development of health services. At this time at RS X based on the Quality of Medical Records, the completeness of filling in the Medical Records of inpatients for the period January –Desember 2023 is still 59%. The purpose of this study was to analyze the compliance analysis of doctors filling out patients Medical Records at the inpatient installation of RS X Jakarta in 2023.The study was conducted with a cross sectional design, using a sample of 60 specialist doctors at RS X. Data were analyzed by Chi Square. Sources of Data This research is primary data collected by the method of distributing questionnaires as a research instrument.The results of the study concluded that there was a significant relationship between age, gender, knowledge, attitudes and motivation of doctors with compliance in filling out medical records with p-value ˂ 0.05. There is no significant relationship between tenure and compliance in filling out medical records with p-value = 0.452 ˃ 0.05. The most dominant relationship in physician compliance in filling out medical records is Doctor's Knowledge and Motivation with p-value = 0.000 ˂ 0.05. Dominance of knowledge and motivation of doctors in filling out medical records. The suggestion is that the knowledge and motivation of doctors really need to be a concern and the hospital management should consider things related to improving the quality of doctors in filling out medical records. Knowledge improvement in regulatory updates, SOPs and procedures for filling out medical records is very important. The use of electronic medical records can provide great benefits for health services such as hospitals.